Deferasirox in Indian children with thalassemia major: 3 years experience - Mayank Dhamija; Amita Mahajan; Manas Kalra; Anju Virmani (Indian Journal of Medical and Paediatric Oncology)
Objective: To evaluate the efficacy and safety of the oral iron chelator deferasirox in treating transfusional hemosiderosis in a cohort of Indian children with thalassemia major with high iron load. Materials and Methods: The first 50 children (age 2-18 yrs) with thalassemia major to commence deferasirox at our center were enrolled and followed up for a period of 36 months between April 2008 and March 2011. The dose of deferasirox was determined by their baseline serum ferritin and was adjusted to a maximum of 40 mg/kg/day depending on response. Ferritin levels, SGOT, SGPT, serum creatinine and urine albumin were regularly monitored. Results: Of the 50 patients, 76% documented a significant decline in serum ferritin ( P<0.05). Seven (14%) patients had a stable ferritin whilst 5 patients (10%) documented an increase over the study period. The mean serum ferritin at baseline, 12, 24 and 36 months was 4354, 3260, 3290 and 3042, respectively ( P<0.05). The median serum ferritin at the same time points was 3555, 2810, 2079 and 2271, respectively ( P<0.05). No severe toxicity was seen. Conclusions: Deferasirox, when given in doses ≥30 mg/kg, was found to be an effective and safe drug in reducing transfusional hemosiderosis. Thirty five (70%) needed dose escalation upto 40 mg/kg/day. Fifteen (30%), however did not achieve a negative iron balance despite maximally permissible doses.